Purification and partial characterisation of a protease inhibitor from Mimosa diplotricha - Zazali Alias,; Nora Asyikin Ramli, (Penerbit Universiti Kebangsaan Malaysia, 2022)
Search for inhibitors to insect proteases is one of many strategies to control pests. Previous work has demonstrated successful purification of effective inhibitors from plant origin. Thus, the current study attempted to purify protease inhibitors from locally available medicinal plants. The study demonstrated that the ethanolic extracts of Mimosa diplotricha leaves caused a significant 80% reduction in bovine trypsin activity. The inhibitory property of the proteinaceous nature of the extract was reconfirmed through qualitative analysis using the detection of trypsin inhibitors on the SDS-PAGE technique. The ammonium precipitated trypsin inhibitor was purified using Hi-Trap G25 and resolved into a single band with a molecular weight of approximately 20.8 kDa. By using the Dixon plot the competitive inhibitor has a Ki value of 2.16 × 10-4 mM. The purified protein inhibited the protease extract of Chrysomya megacephala at IC50 of 28 μg/mL. The results highlighted the presence of trypsin inhibitor in Mimosa diplotricha and its potential as a pest control agent.